Research Brief One-Sheet No.5: Police Criminal Misuse of Conductive Energy Devices - Liederbach, John (2013)
The purpose of the research is to explore and describe the nature and character of arrest cases that involve the criminal misuse of TASERS by police officers through a content analysis of news articles. The research specifically focuses on factors that were common among the arrest events involving CEDs, especially with regard to the actions and motivations of the arrested officers and how the situational context appeared to influence the criminal misconduct of police officers